Penerapan strategi penanggulangan penanganan PTSD (Post Traumatic Stress Disorder) pada anak-anak dan remaja - Ira Palupi Inayah Ayuningtyas (1st ASEAN School Counselor Conference on Innovation and Creativity in Counseling)
Coping strategy is a strategy to overcome the negative emotions that accompany it (Emotion Focused Coping). Handling or counseling the counselor in facing clients who experience PTSD, especially by children or adolescents who require intervention to apply coping strategies in patients with PTSD and counselors collaborate with parents as the closest people. Crisis counseling services using coping strategies is one of the efforts to help trauma victims or clients in crisis conditions using counseling approaches. The purpose of crisis counseling or traumatic counseling is to help restore psychological conditions so that clients gain an understanding of the events and receive traumatized feelings, free from post-traumatic disorders, realistic thinking that trauma is part of the journey of life, normally returning (Resilience). Therefore, the counselor needs to have a thorough understanding of the client's crisis conditions in overcoming the traumatic symptoms that arise. So counselor can provide the right strategy in dealing with PTSD sufferers.